Anger rumination mediates the relationship between reinforcement sensitivity and psychopathology: Results of a 5-year longitudinal study. (1st May 2017) - Izadpanah, Shahrzad; Schumacher, Maren; Barnow, Sven
Highlights: We tested a SEM model with BIS/BAS predicting psychopathology, and anger rumination as mediator BIS predicted higher anxiety and depression, and BAS predicted higher aggression scores BIS × BAS interaction only predicted anxiety symptoms Angry memories and thoughts of revenge mediated the link between BIS and psychopathology Implications for importance of cultivating forgiveness in individuals with high BIS sensitivity